A pioneer experience in Malaysia on In-house Radio-labelling of 131I-rituximab in the treatment of Non-Hodgkin's Lymphoma and a case report of high dose 131I-rituximab-BEAM conditioning autologous transplant - Jew, Win Kuan; Chiong, Soon Law; Xiang, Qi Wong; Ching, Tiong Ko; Zool, Hilmi Awang; Lee, Ping Chew; Kian-Meng, Chang (Elsevier Ltd., 2016)
Radioimmunotherapy is an established treatment modality in Non-Hodgkin's lymphoma. The only two commercially available radioimmunotherapies – 90Y-ibritumomab tiuxetan is expensive and 131I-tositumomab has been discontinued from commercial production. In resource limited environment, self-labelling 131I-rituximab might be the only viable practical option. We reported our pioneer experience in Malaysia on self-labelling 131I-rituximab, substituting autologous haematopoietic stem cell transplantation (HSCT) and a patient, the first reported case, received high dose 131I-rituximab (6000 MBq/163 mCi) combined with BEAM conditioning for autologous HSCT.